Analysis of axial shortening induced by orthokeratology lenses and its mechanical mechanisms - Zhao-Yang Meng; Lin Yang; Peng Zhou (PLoS ONE, 2025)
Purpose This study aims to examine the short-term axial shortening effects of orthokeratology (ortho-K) lenses and investigate their mechanical mechanisms. Methods We conducted a retrospective analysis on 80 myopic children, aged 8–18, who wore ortho-K lenses for one week. Axial lengths were measured pre- and post-treatment using AL-Scan Optical Biometer. We developed a finite element model of the eye using ABAQUS software to explore mechanical changes. Results A significant reduction in axial length was observed after one week of ortho-K lens wear, with an average decrease of 0.028 ± 0.032 mm (P = 4.02 x 10-11). Approximately 82.5% of participants exhibited axial length reduction. The biomechanical model indicated that ortho-K lenses exerted forces altering the tension dynamics within the ocular structure, notably decreasing tension in the posterior ciliary muscle-lens complex. This differential change in tension may account for the mechanical basis of the observed short-term reduction in axial length. Conclusion Orthokeratology lenses induce a short-term shortening in axial length, likely due to mechanical changes in ocular tension dynamics. The finite element model suggests that these lenses decrease posterior ciliary-lens complex tension, leading to axial shortening. These findings enhance comprehension of the mechanical basis for myopia control via ortho-K treatment, highlighting potential avenues for further applied research in myopia management.